2014
DOI: 10.1158/1055-9965.epi-13-1380
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial to Increase Discussion of Breast Cancer in Primary Care

Abstract: Background Assessment and discussion of individual risk for breast cancer within the primary care setting are crucial to discussion of risk reduction and timely referral. Methods We conducted a randomized controlled trial of a multiethnic, multilingual sample of women ages 40 to 74 years from two primary care practices (one academic, one safety net) to test a breast cancer risk assessment and education intervention. Patients were randomly assigned to control or intervention group. All patients completed a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…12 A pragmatic trial of a free-standing, breast cancer–focused risk assessment tool in primary care found improvements in discussion of breast cancer risk and also speaking with a genetic counselor. 13 Several platforms assess risk based on family history alone. 14,15 A pragmatic trial of web-based Family Healthware was associated with improvements in risk perception, and modest increases in self-reported physical activity and fruit and vegetable intake, but a reduced likelihood of receiving cholesterol screening.…”
Section: Discussionmentioning
confidence: 99%
“…12 A pragmatic trial of a free-standing, breast cancer–focused risk assessment tool in primary care found improvements in discussion of breast cancer risk and also speaking with a genetic counselor. 13 Several platforms assess risk based on family history alone. 14,15 A pragmatic trial of web-based Family Healthware was associated with improvements in risk perception, and modest increases in self-reported physical activity and fruit and vegetable intake, but a reduced likelihood of receiving cholesterol screening.…”
Section: Discussionmentioning
confidence: 99%
“…Data were included from all participants who completed the baseline interview for the BreastCARE study, which tested a breast cancer risk reduction education intervention among women scheduled for an appointment with their primary care doctor at SFGH or UCSF’s general medicine practices [23]. Women completed the risk assessment questionnaire by telephone or tablet computer in their preferred language (English, Spanish, or Chinese) before their appointment in 2011–2012.…”
Section: Methodsmentioning
confidence: 99%
“…RST scores were computed for S1; the RST score had been computed previously for S2 [23]. When computing the 6 Point Scale and the RST from S1, we assumed that an entry in the column labeled “diagnosed before age 50?”, which is next to the column labeled “breast cancer” (Figure 2), referred to age at diagnosis of breast cancer for females whether or not there was an entry in the adjacent “breast cancer” box.…”
Section: Methodsmentioning
confidence: 99%
“…While there have been concerns of a Bdigital divide^be-cause of more limited access to the Internet by minorities and lowsocioeconomic status (SES) populations, recent data show that racial gaps in internet and smartphone access have declined [35]. Studies have demonstrated that breast cancer risk assessment can be done online and implemented through mammography and primary care sites [36]. Websites focused on BRCA1/2 risk assessment (e.g., https://www.knowBRCA.org and http://www.…”
Section: Potential Strategies To Address Disparities In Testingmentioning
confidence: 99%